Stable marriage, household consumption and unobserved match quality - Martin James Browning; Laurens Cherchye; Thomas Demuynck; Bram De Rock; Frederic Vermeulen (Institute for Fiscal Studies (IFS), 2021)
We present a methodology for the structural empirical analysis of household consumption and time use behaviour under marital stability. Our approach is of the revealed preference type and non-parametric, meaning that it does not require a prior functional specification of individual utilities. Without making use of the transferable utility assumption, but still allowing for monetary transfers, our method can identify individuals' unobserved match qualities and quantify them in money metric terms. We can include both preference factors, affecting individuals' preferences over private and public goods, and match quality factors, driving differences in unobserved match quality. We demonstrate the practical usefulness of our methodology through an application to the Belgian MEqIn data. Our results reveal intuitive patterns of unobserved match quality that allow us to rationalise both the observed matches and the within-household allocations of time and money.
Keywords: C14; D11; C78; 330; household consumption; marital stability; unobserved matchquality; revealed preference analysis; intrahousehold allocation